Getting Out of the Trap of War on Drugs - Erwinton Simatupang (Magister Administrasi Publik, 2016)
The aim of this paper is to reveal several factors why war on drugs is still adopted by The Indonesian government and to offer an alternative approach as a problem solver. Therefore, the paper utilizes a literature review by collecting data from books, journals, news articles, and research reports. The results indicate that some factors consist of: (a) The New Order as previous generation failed to notice the dangers of drugs; (b) Since the New Order, the government is not committed to reveal the involvement of political actors in the drug problem; (c), SBY did not show a firm attitude to the drug problem; (d), Jokowi is the product of the previous generation, the New Order, who may believe that drug issues can be solved by legal approach; (e) Political affiliation between Jokowi and Megawati at PDI-P; (f) The war on drugs is a populist policy and can not be separated from political interests. As a result, war on drugs in Indonesia is war on young generation because the greatest victim of the policy is the lives of the young generation. To get out of this trap, the government should prevent individuals and groups from social exclusion because social dimensions frequently precede the drug issues and become a stumbling block for those who are addicted to get out of the drug problem.